Appraisement of glocalisation in the context of Nigeria’s foreign policy: A concentric approach - Gideon I. Folorunso; Moses M. Duruji; Felix C Chidozie (Cogent Arts & Humanities)
This paper examines the nexus between Nigeria’s foreign policy and glocalisation. Glocalisation is an emerging concept in foreign policy discourse, with the sole intent of forging a synergy between globalisation, global governance, and local relations, hinging on domestic peculiarities. As it were, foreign policy has largely projected the interest of the ruling class and other private interests rather than the greater good regardless of the gains for the ruling elites, as posited by Jeremy Bentham. The concentric model was the theoretical framework used by the study to explain the levels of relation from the core to the periphery, a globalised foreign policy to a glocalised foreign policy. Qualitative research methods were adopted for this study, using secondary sources of data collection, and textual analysis. While little or no attention has been paid to glocalisation efforts in foreign policy discourse in Africa, it has been on the table of discussion for the western world, notwithstanding the current level of development occasioned by diplomatic relations worldwide. Progressively, within foreign policy discourses, the need to glocalise foreign policy cannot be overemphasised, as it marks the beginning of real polity as explained by Aristotle, as against simply focusing on the localisation of globalisation.